Development Of Professional And Methodological Competence Of Teachers (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article provides information on the development of professional and methodical competence of future elementary school teachers, ways of teacher self-improvement and ability development.